Copper‐Catalyzed Oxidative Cascade Inter‐Molecular Double Cyclization of 2‐Iodobenzamide Derivatives and Propargyl Dicarbonyl Compounds for Accessing 3‐Hydroxy‐3‐Furylisoindolinone Derivatives. Issue 16 (19th July 2022) - Kavala, Veerababurao; Lin, Li‐Chun; Bhimrao Patil, Prakash; Fang, Chia‐Chi; Hong, Zih‐Yu; Liou, Yi‐Ru; Chen, Yu‐Nong; Weng, Yin‐Zhi; Sarathkumar, Sundaramoorthi; Sambasiva Rao, Naidu; Suresh, Sundaram; Jiang, Zongyan; et al.
Abstract: A one‐pot strategy for the synthesis of 3‐hydroxy‐3‐furylisoindolinone derivatives is reported. The reaction proceeds via a copper‐catalyzed oxidative cascade inter‐molecular double cyclization of 2‐iodobenzamide derivatives and propargyl dicarbonyl compounds in the presence of oxygen. The strategy involves several reactions including cyclization/coupling/double C( sp3 )− H functionalization in a cascade manner. A wide range of 2‐iodobenzamide substrates containing different substituents as well as various propargyldicarbonyl compounds and propargylsulfonyl aryl ketones can be used to access a variety of 3‐hydroxy‐3‐furylisoindolinone derivatives. Abstract :